Implementasi Sistem Informasi Akuntansi Penggajian dan Dampaknya Terhadap Kinerja Karyawan pada Bank Muamalat Cabang Gorontalo - Bakri Bakri (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2020)
This study aims to determine impact the implementation of the Payroll Accounting Information System on Employee Performance at Bank Muamalat Gorontalo Branch. The method used in this research is quantitative by using a survey approach with a population of 22 people at Bank Muamalat Gorontalo Branch. Testing is done by simple regression. The results prove that the Payroll of Accounting Information System has a positive and significant effect on Employee Performance (Y) at Bank Muamalat Gorontalo Branch, amount to 94.9%. and the remaining 5.1% is influenced by other variables that have not been studied, such as variables of organizational culture and wages. The results of this study prove that employees are assets and are an important resource in building company performance. Therefore, companies must be able to provide appreciation and motivation to employees, such as providing incentives and allowances. If employees feel satisfied with what they get from the company, loyalty will arise in the employees and employee performance will be better and increase.